2011
DOI: 10.1152/ajprenal.00470.2010
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression profiling in early-stage polycystic kidney disease in the Han:SPRD Cy rat identifies a role for RXR signaling

Abstract: Han:SPRD Cy is a spontaneous rat model of polycystic kidney disease (PKD) caused by a missense mutation in Pkdr1. Cystogenesis in this model is not clearly understood. In the current study, we performed global gene expression profiling in early-stage PKD cyst development in Cy/Cy kidneys and normal (+/+) kidneys at 3 and 7 days of postnatal age. Expression profiles were determined by microarray analysis, followed by validation with real-time RT-PCR. Genes were selected with over 1.5-fold expression changes com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The quality and concentration of each sample was confirmed by spectrophotometry (NanoDrop ND-1000; Asahi glass Co. Ltd., Tokyo, Japan). Total RNA obtained from three females was pooled in each PIO-treated or control vehicle-treated (CONT) group in accordance with our previous report [11]. …”
Section: Methodsmentioning
confidence: 99%
“…The quality and concentration of each sample was confirmed by spectrophotometry (NanoDrop ND-1000; Asahi glass Co. Ltd., Tokyo, Japan). Total RNA obtained from three females was pooled in each PIO-treated or control vehicle-treated (CONT) group in accordance with our previous report [11]. …”
Section: Methodsmentioning
confidence: 99%
“…Retinoid X receptor (RXR): recently, we reported that the rXr-mediated pathway is upregulated in the cy rat model [22]. This finding suggests that the regulation of this pathway may control PKD progression through cell proliferation mechanisms in this model.…”
Section: Other Signaling Cascadesmentioning
confidence: 96%
“…Differential expression was confirmed in only 74 genes, 12 of which showed discordant (opposite) results with the SAGE patterns. Other studies are less straightforward in the description of their methods, and in a few cases the number of samples is not even reported 20, 21, 22 .Analysis: while one should be able to assume that the data were properly analyzed, it is not necessarily realistic to expect that the reviewers for every publication re-analyzed the data and confirmed the results. In fact, it is not safe to assume that data are available, nor that, if available, the results can be reproduced, as a repeatability study by Ioannidis et al showed 23 .…”
Section: ‘Omics’ Datamentioning
confidence: 99%
“…Differential expression was confirmed in only 74 genes, 12 of which showed discordant (opposite) results with the SAGE patterns. Other studies are less straightforward in the description of their methods, and in a few cases the number of samples is not even reported 20, 21, 22 .…”
Section: ‘Omics’ Datamentioning
confidence: 99%